2023
DOI: 10.3389/fvets.2023.1196955
|View full text |Cite
|
Sign up to set email alerts
|

Participatory assessment of management and biosecurity practices of smallholder pig farms in North East India

Mahak Singh,
Nungshitula Pongenere,
R. T. Mollier
et al.

Abstract: The present study was aimed at describing the pig production system, farm management, pig movement, and existing biosecurity level of smallholders' pig production system in North East India. A cross-sectional survey of 1,000 pig producers in four districts (two urban and two rural) in core pig-producing regions of India, where ASF occurrence had been reported, was conducted. The mean pig population was significantly (p < 0.05) higher in urban districts. In urban districts, most of the pig houses were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Theory and related research have demonstrated that basic biosecurity measures include factors such as location and layout, production processes, feed types, daily disinfection, the treatment of dead pigs, management strategies, and infrastructure construction rules and regulations [41][42][43][44][45][46][47]. Based on the related research, the biosecurity level in this study was assessed on five aspects: (1) Breeding environment management, which comprised both offsite and on-site environmental controls, such as scientific site selection, optimized layout, reasonable zoning, regular rodent control, mosquito control, fly control, and the prohibition of unrelated animals; (2) breeding process management, which comprised inputs such as feeding, and slaughter management, formal source channels for pig breeds, feed, medicines and other inputs, appropriate storage to meet the requirements, standardized and orderly breeding operations, breeding file records, and live pig supervision; (3) personnel and vehicle management that met the requirements and complete admission procedures; (4) decontamination and waste treatment, such as cleaning, disinfection, waste treatment, cleaning and disinfection equipment, the timely disinfection of foreign and contaminated objects, and the harmless treatment of aquaculture waste; and (5) biosecurity awareness, such as ASF prevention and biosecurity management awareness regarding ASF and related biosecurity knowledge, epidemic handling procedures, and the importance of improving biosecurity.…”
Section: Construction Of Biosecurity Indexmentioning
confidence: 99%
“…Theory and related research have demonstrated that basic biosecurity measures include factors such as location and layout, production processes, feed types, daily disinfection, the treatment of dead pigs, management strategies, and infrastructure construction rules and regulations [41][42][43][44][45][46][47]. Based on the related research, the biosecurity level in this study was assessed on five aspects: (1) Breeding environment management, which comprised both offsite and on-site environmental controls, such as scientific site selection, optimized layout, reasonable zoning, regular rodent control, mosquito control, fly control, and the prohibition of unrelated animals; (2) breeding process management, which comprised inputs such as feeding, and slaughter management, formal source channels for pig breeds, feed, medicines and other inputs, appropriate storage to meet the requirements, standardized and orderly breeding operations, breeding file records, and live pig supervision; (3) personnel and vehicle management that met the requirements and complete admission procedures; (4) decontamination and waste treatment, such as cleaning, disinfection, waste treatment, cleaning and disinfection equipment, the timely disinfection of foreign and contaminated objects, and the harmless treatment of aquaculture waste; and (5) biosecurity awareness, such as ASF prevention and biosecurity management awareness regarding ASF and related biosecurity knowledge, epidemic handling procedures, and the importance of improving biosecurity.…”
Section: Construction Of Biosecurity Indexmentioning
confidence: 99%